MADRASAH DINIYAH DAN TRADISI KEAGAMAAN SANTRI DI INDONESIA - YUSRIL RUBIANTARA ABAS; KHALID F HAMZAH; HAQQAN FADLAN SILEUW (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
This article describes the challenges and existence of Madrasah diniyah (Madin) as an Islamic religious education institution that provides many parts for the development of education in Indonesia. The existence of Islamic schools as institutional entities of Islamic religious education in Indonesia has faced challenges from time to time. From the historical aspect of its development, madrasah diniyah grew and developed along with the development of Islam in the country. Government policies in the development of madrasah diniyah undergo changes in line with government policies in the implementation of the national education system. In general, madrasah diniyah government policies are looser than other types of formal education. The latest dynamics of Madrasah diniyah are marked by the birth of the Formal Diniyah Education institution (PDF), a religious education unit that has a curriculum of 80% Islamic religious science and 20% general science and its graduates will be formally recognized by the state.